PENGARUH VARIABEL KEBUTUHAN FISKAL TERHADAP ALOKASI DAU DI INDONESIA - Azwardi Azwardi (Jurnal Ekonomi Pembangunan, 2006)
The aim of this research is to know the influence of fiscal needs to allocation Dana Alokasi Umum (DAU). Fiscal needs are population, area of province, density, construction index, the poverty allo and government index. Based on the regression that use scunder data we know that population and government expenditure are positif, but other variable is negative. Keywords: fiscal needs, dana alokasi umum (DAU)